2015
DOI: 10.1186/s12931-015-0287-2
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte senescence in COPD is associated with decreased histone deacetylase 2 expression by pro-inflammatory lymphocytes

Abstract: BackgroundHistone acetyltransferases (HAT) and histone deacetylases (HDAC) are enzymes that upregulate and down-regulate pro-inflammatory gene transcription respectively. HDAC2 is required by corticosteroids to switch off activated inflammatory genes and is reduced in lung macrophages in COPD. We have shown that COPD patients have increased steroid resistant CD28null (senescent) pro-inflammatory T and NKT-like peripheral blood cells (particularly CD8+ subsets) and we hypothesized that these changes would be as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 29 publications
11
50
0
Order By: Relevance
“…Hsp70, perforin and granzyme B expression by CD28+ and CD28null T and NKT-like cells A higher percentage of CD28nullCD8+ T cell and NKTcells expressing perforin and granzyme b was found in COPD patients compared with control subjects (eg., 44 ± 12 (15 ± 13) p = .031; and 34 ± 11 (13 ± 9) p = .021 for the percentage of CD28null CD8+ T cells expressing granzyme b and perforin (median ± sem) from COPD patients (controls) respectively, consistent with a previous report [9]. There was no change in perforin or granzyme b expression in CD28 + CD8+ or CD28 + CD8-T and NKT-like cells from COPD or control groups (p > 0.05 for all) also consistent with a previous report [9].…”
Section: Increased Cd28null Cd8+ T and Nkt-like Cells In Copd Patientssupporting
confidence: 90%
See 1 more Smart Citation
“…Hsp70, perforin and granzyme B expression by CD28+ and CD28null T and NKT-like cells A higher percentage of CD28nullCD8+ T cell and NKTcells expressing perforin and granzyme b was found in COPD patients compared with control subjects (eg., 44 ± 12 (15 ± 13) p = .031; and 34 ± 11 (13 ± 9) p = .021 for the percentage of CD28null CD8+ T cells expressing granzyme b and perforin (median ± sem) from COPD patients (controls) respectively, consistent with a previous report [9]. There was no change in perforin or granzyme b expression in CD28 + CD8+ or CD28 + CD8-T and NKT-like cells from COPD or control groups (p > 0.05 for all) also consistent with a previous report [9].…”
Section: Increased Cd28null Cd8+ T and Nkt-like Cells In Copd Patientssupporting
confidence: 90%
“…Senescent CD28null T and NKT-like cells have been shown to be more pro-inflammatory and cytotoxic than their CD28 positive counterparts [6,9,10], and exhibit a relative resistance to corticosteroids [10]. Increased proinflammatory CD8+ T cells in peripheral blood and lungs [4] and an increase in cytotoxic NKT-like and NK cells in the airways have been shown in COPD patients compared to healthy and never-smokers [7].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the glucocorticoid receptor (GCR) has recently been shown to be decreased in pro‐inflammatory T and NKT‐like cells post‐lung transplant which may help to explain steroid resistance following lung transplant . Interestingly, HDAC2 has been shown to be decreased in macrophages in COPD and recently in lymphocytes, another progressive chronic inflammatory lung disease also shown to be associated with increased cytotoxic pro‐inflammatory T and NKT‐like cells similar to our findings for lung transplant patients …”
Section: Introductionmentioning
confidence: 99%
“…HDAC2 is required by corticosteroids to switch off activated inflammatory genes and is reduced in lung macrophages in COPD (10). A recent study showed that HDAC2 expression was suppressed in pro-inflammatory CD8 + CD28 null NKT-like cells in patients with COPD (19) and negatively correlated with the percentage of CD8 + CD28 null NKT-like cells producing IFNγ or TNFα in all subjects (e.g., COPD: R  = −0.789, p  < 0.001 for CD8 + CD28 null NKT-like cells producing IFNγ) (Figure 2D). Theophylline is an activator of HDAC and enhances the anti-inflammatory effects of corticosteroids in alveolar macrophages in COPD patients (20).…”
Section: Steroid Resistance In Cd8+cd28null Nkt-like Cells In Copdmentioning
confidence: 83%